1999
DOI: 10.1143/jjap.38.l1087
|View full text |Cite
|
Sign up to set email alerts
|

Control of Crystallization at Low Thickness in µc-Si:H Films Using Layer-by-Layer Growth Scheme

Abstract: Hydrogen plasma treatment of stacking layers in a layer-by-layer (LBL) growth scheme effectively modulates the network structure from the surface into the bulk through the growth zone by abstraction of hydrogen from the Si:H matrix. It is an efficient way of reducing the microcrystalline transition layer so that virtual saturation of the crystallization may be obtained at a significantly low thickness of the sample compared to that obtained by a continuous mode of deposition. The growth of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…The sharp change in the slope of the overall film deposition rate along with the sharp lowering in the individual thickness of the incubation as well as the surface layer on increasing H dilution (Fig. 3), implies definitely a transformation of the growth pattern in the Si:H network around RðH 2 Þ ¼ 92:75%: Identical sharp change in the film deposition rate has been demonstrated at the phase transition corresponding to the attainment of virtual saturation in crystallinity during increase in thickness of the stacked layer mc-Si:H film deposited by H-plasma exposure of the stacking layers in LBL growth scheme [23]. Composition analysis of the individual layers, by ellipsometry studies, identifies a transition from a mixed phase of (a þ mc)-Si to a mostly mc-Si dominated growth regime at around RðH 2 Þ ¼ 92:75%: However, atomic H induced etching of the crystalline component in the network at RðH 2 Þ .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The sharp change in the slope of the overall film deposition rate along with the sharp lowering in the individual thickness of the incubation as well as the surface layer on increasing H dilution (Fig. 3), implies definitely a transformation of the growth pattern in the Si:H network around RðH 2 Þ ¼ 92:75%: Identical sharp change in the film deposition rate has been demonstrated at the phase transition corresponding to the attainment of virtual saturation in crystallinity during increase in thickness of the stacked layer mc-Si:H film deposited by H-plasma exposure of the stacking layers in LBL growth scheme [23]. Composition analysis of the individual layers, by ellipsometry studies, identifies a transition from a mixed phase of (a þ mc)-Si to a mostly mc-Si dominated growth regime at around RðH 2 Þ ¼ 92:75%: However, atomic H induced etching of the crystalline component in the network at RðH 2 Þ .…”
Section: Discussionmentioning
confidence: 87%
“…By extending in the time space the atomic H reactivity on the growing surface by H-plasma treatment of the stacking layers in the layer-by-layer (LBL) growth scheme, efficient modulation of the structural network and promotion of microcrystallization in Si:H has been demonstrated [2] and mc-Si:H films are obtained at a very low film thickness [23]. Abstraction of hydrogen bonded to Si, breaking of weak Si-Si bonds, chemical etching by SiH 4 formation, recombination, formation of Si -H bonds by rehydrogenation of surface dangling bonds, and diffusion of atomic H into the Si-matrix are the various processes those occur on the growing network during film deposition [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…According to Yamasaki et al [8] with incorporation of boron atoms into the network, several gap states are introduced, which are located energetically close to a band edge that contributes partially to the increase in optical absorption and band gap narrowing. At the onset of phase transition, in general, a sharp increase in structural heterogeneity in the network leads to physical vapor deposition (PVD)-like growth and contributes to a sharp increase in optical absorption by the defect centres [12,13], and that continues at higher doping level. Okamoto et al [14] demonstrated a reduction of optical gap at higher boron doping.…”
Section: Resultsmentioning
confidence: 99%
“…29 As the number of stacking layers was increased, a phase transformation was monitored and we termed the associated layers as microcrystalline-transition layer that developed over the amorphous incubation layers and beyond which the growth of microcrystalline network was initiated and continuously improved. The microcrystalline-transition layer was demonstrated to be highly defective and contained a large number of dangling bonds and voids.…”
Section: Resultsmentioning
confidence: 99%
“…31,32 It is speculated that during the process of microcrystalline growth the network must proceed through microcrystalline-transition state when prepared by changing whatever parameter ͑e.g., rf power in the present case͒, and in any case it proceeds through the amorphous-incubation layer, microcrystalline-transition layer, and then bulk microcrystalline state during its continuous accumulation in growth. 29 Hence, the appearance of structural inhomogeneity in the microcrystalline-transition state, in general, could be closely correlated to the development of microcrystallinity, as if nuclides for microcrystallization originate in the womb of inhomogeneity. It is proposed that PVD-like growth at the microcrystalline-transition state, at increasing rf power in highly Ar diluted SiH 4 plasma, in particular, allows longrange structural relaxation that initiates nucleation to the Si network and accelerates microcrystallization at higher power applied to the plasma.…”
Section: Resultsmentioning
confidence: 99%